2018
DOI: 10.1016/j.scitotenv.2017.08.134
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal exposure to incense burning and blood pressure during pregnancy

Abstract: Incense burning is a popular practice in Asian and Arabic countries. Previous studies show that incense burning was associated with increased risks of adverse outcomes among non-pregnant population. However, very few studies explored its health effects among pregnant women, who are more susceptible to environmental stressor. We aimed to examine the association between incense burning at home and hypertensive disorders as well as blood pressure levels during pregnancy, using data from 10,563 pregnant women recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…For the continuous variables (including PM 2.5 exposure, BMI, and age), PM 2.5 exposure was found significantly and positively correlated with SBP (p < 0.05) Figure 5A but was not significantly correlated with DBP Figure S2A), which is consistent with previous studies. 22,50 A previous study also found only SBP of pregnant women increased after exposure to incense burning, 51 Therefore, the partial effects of various influencing factors and their relative contributions to the total variance of blood pressures were explored based on the GLM coupled with dominance analysis Figure 6, Figure S3, Table S2, and Table S3. It was found that the age of the rural residents was positively and significantly associated with SBP and DBP (all p < 0.05) and the BMI was only positively and significantly associated with SBP (p < 0.05).…”
Section: Impacts Of Various Factors On Blood Pressuresmentioning
confidence: 99%
“…For the continuous variables (including PM 2.5 exposure, BMI, and age), PM 2.5 exposure was found significantly and positively correlated with SBP (p < 0.05) Figure 5A but was not significantly correlated with DBP Figure S2A), which is consistent with previous studies. 22,50 A previous study also found only SBP of pregnant women increased after exposure to incense burning, 51 Therefore, the partial effects of various influencing factors and their relative contributions to the total variance of blood pressures were explored based on the GLM coupled with dominance analysis Figure 6, Figure S3, Table S2, and Table S3. It was found that the age of the rural residents was positively and significantly associated with SBP and DBP (all p < 0.05) and the BMI was only positively and significantly associated with SBP (p < 0.05).…”
Section: Impacts Of Various Factors On Blood Pressuresmentioning
confidence: 99%
“…Due to their small size, incense smoke particles can penetrate deeply into the lungs and settle in the respiratory system. He et al [12] also reported the association between incense burning and the risk of hypertensive disorders and blood pressure levels during pregnancy. Zhou et al [13] claims that burning incenses is higher cytotoxicity and genotoxicity than burning cigarette.…”
Section: Introductionmentioning
confidence: 97%
“…[15][16][17][18] However, the slow and incomplete combustion process produces multiple indoor air pollutants, [19][20][21][22][23] such as polycyclic aromatic hydrocarbon (PAH) and other components of particulate matter (PM), which have been linked with deleterious health outcomes. 15,17,[19][20][21]23 Moreover, incense burning exposure during late pregnancy was found to be associated with increased risk of maternal hypertensive disorder, 24 along with the possible adverse health effects of asthma and respiratory tract symptoms, 18 decreased head circumference and body weight, 16 and delayed gross motor milestone development among term singletons. 25 These findings were in line with previous findings of particulate matters and polycyclic aromatic hydrocarbon in air pollution exposure and adverse birth outcomes like preterm birth and inferior neurodevelopmental status among infants and children.…”
Section: Introductionmentioning
confidence: 99%